Workplace Bullying Among Senior Medical Staff in Africa: Prevalence, Impact, and Contributing Factors - Katrien Lodhe L; Alleksand Montes; Zachari Diallofd Diallofd (Inovasi Analisis Data, 2024)
Objective: This cross-sectional quantitative study aimed to establish the prevalence, antecedents, and outcomes of workplace bullying among senior medical staff in Africa. It will look at how workplace demands, peer and managerial support and bullying affects personal and professional outcomes.Methods: We used a mixed methods approach with quantitative surveys and qualitative interviews in several African healthcare settings. The prevalence of bullying was measured using the Negative Acts Questionnaire (NAQ-r), and the level of workplace demands and support for individuals was assessed using the Health and Safety Executive Management Standards Analysis Tool.Findings: The new study found that 38% of senior doctors reported experiencing bullying on a weekly basis and even higher rates in emergency medicine and related specialties. Bullying was significantly associated with high workplace demands and low peer and managerial support. So far-reaching were the ramifications of his bullying that they undermined both individual welfare and organizational efficacy. In other words, 69.6% of responses did not indicate bullying because of alleged reasons of barriers for reporting like fear of retaliation, and lack of trust in management whatsoever.Novelty: This study offers unprecedented insights into a hitherto neglected area workplace bullying in African healthcare. It showcases novel contributing aspects, including workload and support systems, while shedding light on the barriers to reporting, providing a new lens of contention in African contexts.Research Implications: Its findings highlight the importance of schools' implementing interventions to reduce workplace bullying, including promoting supportive infrastructures, managing demands and stressors in the workplace, and creating environments for safe reporting, to protect the well-being of Africa's senior medical professionals.